Pengaruh Harga, Kualitas Produk, Dan Citra Merek Terhadap Keputusan Pembelian Pada E-commerce Shopee (Studi Kasus Mahasiswa Universitas Islam Malang) - Muhammad Tyas Fariskal Ardiannyash; Agus Widarko; Afi Rachmat Slamet (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to determine and analyze the effect of price, product quality and brand image on purchasing decisions in e-commerce Shopee. This research used a case study of students at the Islamic University of Malang who were selected by purposive sampling. Determination of the number of samples using the Malholtra formula and the results obtained were 90 respondents. Data analysis methods used in this study are Instrument Test (validity test and reliability test), Normality Test, Classical Assumption Test (multicollinearity test and heteroscedasticity test), Multiple Linear Regression Analysis, Hypothesis test (F test and t test), and Test Coefficient of Determination (Adjusted R2). Process analysis using SPSS. The results of the study stated that price, product quality and brand image simultaneously had an effect on purchasing decisions and price had no partial effect on purchasing decisions while product quality and brand image had a partial positive and significant effect on purchasing decisions.